The Lysine Methyltransferase SMYD2 Is Required for Definite Hematopoietic Stem Cell Production in the Mouse Embryo - Melissa A. Edwards; Mark A. Brown; Ilham Alshiraihi; Dillon K. Jarrell; Haley O. Tucker (Veterinary Sciences, 2020)
The five-membered SET and MYND domain-containing lysine methyltransferase (SMYD) family plays pivotal roles in development and differentiation. Initially characterized within the cardiovascular system, one such member, SMYD2, has been implicated in transcriptional and apoptotic regulation of hematopoiesis. Deletion of Smyd2 in adult mouse Hemaopoietic Stem Cells (HSC) using an interferon-inducible mx1-Cre-mediated conditional knockout (CKO) led to HSC reduction via both apoptosis and transcriptional deficiencies. Since HSC are specified from hemogenic endothelial (HE) cells in the dorsal aorta (DA), we sought to determine whether the flaw in HSC originated embryologically from this site. Toward this end, we performed deletion with vav-Cre mice, which is active in all hematopoietic and endothelial tissues from E10.5 embryonic life onward. Unexpectedly, we observed no defects in the embryo, other than apoptotic loss of definite HSC, whereas adult hematopoietic populations downstream were unaffected. These results further establish the importance of SMYD2 in antiapoptotic gene control of gene expression from the embryo to the adult.